Possible Interactions of Extracellular Loop IVP2-S6 With Voltage-Sensing Domain III in Cardiac Sodium Channel - Zaytseva, Anastasia K.; Boitsov, Aleksandr S.; Kostareva, Anna A.; Zhorov, Boris S. (Frontiers in Pharmacology, 2021)
Motion transmission from voltage sensors to inactivation gates is an important problem in general physiology of ion channels. In a cryo-EM structure of channel hNav1.5, residues N1736 and R1739 in the extracellular loop IVP2-S6 approach, respectively, glutamates E1225 and E1295 in the voltage-sensing domain III (VSD-III). ClinVar-reported variants E1230K, E1295K and R1739W/Q and other variants in loops IVP2-S6, IIIS1-S2 and IIIS3-S4 are associated with cardiac arrhythmias, highlighting the interface between IVP2-S6 and VSD-III as a hot spot of disease mutations. Atomic mechanisms of the channel dysfunction caused by these mutations are unknown. Here we generated mutants E1295R, R1739E, E1295R/R1739E and N1736R, expressed them in HEK-293T cells, and explored biophysical properties. Mutation E1295R reduced steady-state fast inactivation and enhanced steady-state slow inactivation. In contrast, mutation R1739E slightly enhanced fast inactivation and attenuated slow inactivation. Characteristics of the double mutant E1295R/R1739E were rather similar to those of the wild type channel. Mutation N1736R attenuated slow inactivation. Molecular modeling predicted salt-bridging of R1739E with the outermost lysine in the activated-state voltage-sensing helix IIIS4. In contrast, the loss-of-function substitution E1295R repelled R1739, thus destabilizing the activated VSD-III in agreement with our data that E1295R caused a depolarizing shift of the G/V curve. In-silico deactivation of VSD-III with constraint-maintained salt bridge E1295-R1739 resulted in the following changes: (i) contacts between IIIS4 and IVS5 were switched; (ii) contacts of the linker-helix IIIS3-4 with IVS5, IVS6 and fast-inactivation tripeptide IFM were modified; (iii) contacts of the IFM tripeptide with helices IVS5 and IVS6 were altered; (iv) mobile loop IVP2-S6 shifted helix IVP2 that contributes to the slow-inactivation gate and helix IVS6 that contributes to the fast-inactivation gate. The likelihood of salt bridge E1295-R1739 in deactivated VSD-III is supported by Poisson-Boltzmann calculations and state-dependent energetics of loop IVP2-S6. Taken together, our results suggest that loop IVP2-S6 is involved in motion transmission from VSD-III to the inactivation gates.